Tank linings for chemical process industries - Chandrasekaran, V. C. (ISmithers, 2009)
Rubber linings can be used as passive protection against the corrosion of plant and equipment in the chemical process industries. Rubbers act as sacrificial materials reacting or un-reacting with the corrosive media, diffusing the liquids or not diffusing, swelling by itself or not swelling, permeating or not permeating gases or fumes, abrading or wearing by the slurry particles, getting ozonised or oxidised; but still protecting the metal surface beneath it, during its considerable life cycle under those severe and stressed conditions. Rubbers age but their life cycle is good enough to protec.
Keywords: Rubber coatings.; Tanks -- Linings.; Chemical engineering -- Equipment and supplies.; elektronické knihy; electronic books